Nilotinib-Induced Dystonia and Cognitive Deficits in a Neurologically Normal Patient with Chronic Myeloid Leukemia - Justine Chan; Paarth Shah; Guillermo Moguel-Cobos (Case Reports in Neurological Medicine)
Nilotinib is a tyrosine kinase inhibitor used to treat patients with chronic myeloid leukemia (CML). This agent is also being studied in neurodegenerative disorders including Parkinson disease. Studies have shown that nilotinib may decrease the accumulation of parkin substrates and decrease the loss of dopaminergic cells. The use of nilotinib in neurologic disorders is relatively new, and little information about this use has been published. We report on a patient receiving nilotinib for CML. The patient had no previous neurologic deficits, and developed intermittent dystonic posturing of the left upper extremity and cognitive impairment after she began nilotinib treatment. The mechanisms behind this adverse effect are not clear; however, her symptoms began after nilotinib was introduced, decreased with dose reduction, stopped with its cessation, and re-emerged when the medication was restarted. To our knowledge, this is the first reported patient with neurologic symptoms secondary to nilotinib use.